Global change and the Caribbean : adaptation and resilience - Barker, David, 1947-; McGregor, Duncan F. M.; Rhiney, Kevon; Edwards, Thera (Jamaica : The University of the West Indies Press, 2016)
This is the fifth in a series of volumes published by UWI Press exploring how geographical and cognate research is being applied to address key environmental problems in the Caribbean region. Global Change and the Caribbean highlights how current research is addressing the consequences of change, forced by global warming and climate change, and driven by globalization and population growth. The book takes forward issues of regional and community vulnerability, and focuses on the search for solutions in terms of adaptation, resilience and societal transformation. The question of transformation is debated by authors and the editors in drawing together the prospects for regional and community resilience. The chapters are presented as a series of original, empirical research contributions, which have the common theme of the search for development strategies which focus on social and economic needs of the people without further deterioration of the region's fragile environmental resource base. The book will be essential reading at first degree and masters levels in institutions with Caribbean-focused courses relating to geography, and in multidisciplinary areas such as development studies, social studies, environmental management, planning and resource management. The approaches and case studies presented here will be of significant interest to regional planners, resource management specialists and public sector officials.
Adaptation and Resilience: Changing Caribbean Perspectives / Duncan McGregor, David Barker, Kevon Rhiney and Thera Edwards -- Part 1: Regional, National and Sectoral Approaches: Vulnerability, Adaptation and Resilience -- Caribbean Tourism and Urban Development: Resilience and Adaptation to Global Change over Five Hundred Years / William C. Found -- The 2014 Jamaican Drought: Climate Change or Interannual Climate Variability? / Shaina Poore, Alex A. Moulton, Douglas W. Gamble, Scott Curtis and Jeff Popke -- The Insurance Trap: Banana Farming in Dominica after Hurricane Hugo / Chris Knudson -- A Vulnerability and Capacity Assessment of the Critical Infrastructure of St. Kitts to Projected Impacts of Climate Change / Elmo Burke and Janice Cumberbatch -- Part 2: Community-Level Vulnerability: Adaptive capacity and Social Capital -- Assessing Vulnerability and Resilience to Climate Change in Jamaica: Directions for Community-Based Research in the Caribbean / Kevon Rhiney, Donovan Campbell and David Barker -- Comparative Vulnerabilities and Adaptation Strategies of Caribbean Fishers: The Case of Old Harbour Bay, Jamaica / April K. Baptiste -- Challenge, Change and the Expression of Social Capital in Kingston, Jamaica and Rural St Lucia / Robert Kinlocke and Chanelle Fingal-Robinson -- Social Capital and Rural Resilience among the Carib Communities in Northeastern St Vincent / Rose-Ann Smith -- Part 3: Participatory Approaches: Local Knowledge and Community Resilience -- Relationships between a World Heritage Site and Its Contiguous Communities: A Case Study of Dominica in the International Context / Thomas Klak and Joseph Simonowicz -- Policies and Practices: Identifying Synergies and Conflict for Indigenous Community Sustainability in the Guiana Shield, South America / Jayalaxshmi Mistry, C eline Tschirhart, Andrea Berardi, Odacy Davis, Elisa Bignante, Lakeram Haynes, Ryan Benjamin, Grace Albert, Rebecca Xavier, Bernie Robertson, Deirdre Jafferally, Caspar Verwer, Rob Glastra and G eraud de Ville -- Design Charrettes: An Approach to Community Climate Change Adaptation in Tobago / Luna Khirfan -- Climate Change: Local Perceptions and Adaptation Perspectives from Guyana and Suriname / Paulette Bynoe -- Retrospect and Prospect: The British-Caribbean Geography Seminar Series / David Barker and Duncan McGregor.
Includes bibliographical references.
Keywords: Caribbean Area -- Environmental conditions; Global environmental change; Ecology; Global environmental change; Caribbean Area